Pengaruh Model Literasi Lingkungan Jelajah Alam Sekitar (LiteLJAS) berbantuan Wayground terhadap Motivasi Belajar IPA - Ainul Muslimah; Aulia Azhar; Febri Yanto; Firda Azzahra (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This research investigates the impact of utilizing the Environmental Literacy Learning Model for Exploring the Natural Surroundings (LiteLJAS) through Wayground on the motivation toward science education for seventh-grade students at SMPN 28 Padang. The research employed a quantitative method featuring a Non-Equivalent Control Group Design, which included both an experimental group and a control group. Data gathering was conducted using a motivational survey for learning, an observation form for carrying out the learning process, and a feedback questionnaire for students. The collected data was evaluated through a normality test, a homogeneity test, a t-test, and a t'-test. The findings indicated that the execution of learning was classified in the exceptional tier, reaching a rate of 96%. According to the outcomes of the hypothesis test, the computed t value exceeded the t table value (3.042 > 2.008), indicating that applying the LiteLJAS model in conjunction with Wayground significantly affects students' motivation for science learning. Moreover, students' reactions to learning were categorized as excellent with a rate of 99%. As a result, combining the LiteLJAS model with Wayground has been effective in enhancing students' motivation to learn. Penelitian ini bertujuan untuk menganalisis pengaruh penerapan model pembelajaran Literasi Lingkungan Jelajah Alam Sekitar (LiteLJAS) yang didukung oleh Wayground terhadap motivasi siswa kelas VII dalam belajar IPA di SMPN 28 Padang. Studi ini menggunakan pendekatan kuantitatif dengan Non Equivalent Control Group Design, yang mencakup kelompok eksperimen dan kelompok kontrol. Informasi didapatkan melalui kuesioner motivasi belajar, lembar observasi proses pembelajaran, dan kuesioner respon siswa. Data yang diperoleh dianalisis melalui uji normalitas, uji homogenitas, serta uji t dan t’. Temuan penelitian mengindikasikan bahwa pelaksanaan pembelajaran tergolong sangat baik dengan persentase mencapai 96%. Hasil uji hipotesis menunjukkan bahwa nilai thitung lebih besar dari ttabel (3,042 > 2,008), sehingga dapat disimpulkan bahwa penggunaan model LiteLJAS yang didukung Wayground memberikan dampak signifikan terhadap motivasi belajar IPA siswa. Di samping itu, tanggapan siswa terhadap pembelajaran juga termasuk sangat positif dengan persentase mencapai 99%. Dengan demikian, penerapan model LiteLJAS yang diintegrasikan dengan Wayground terbukti efektif dalam meningkatkan motivasi belajar peserta didik.